Simultaneous presentation of thyroid storm and diabetic ketoacidosis in a previously healthy 21-year-old man - Wallington, David (BMJ Case Rep, 2019)
A 21-year-old young man with no history of diabetes or thyroid disease presented to the emergency department with simultaneous thyroid storm and diabetic ketoacidosis. Notable findings on admission were a ventricular rate of 235 beats/min, tachypnoea, tremors, polydipsia and a lack of fever. Due to the unusual constellation of symptoms, diagnosis was only possible after initial laboratory results came back. While the lack of fever is unusual in thyroid storm, diabetic ketoacidosis has previously been reported to suppress fever, and this case supports the occurrence of this phenomenon. This case was highly unusual because the patient had not previously been diagnosed with either type 1 diabetes or Graves’ disease.